Vous êtes sur la page 1sur 4
t n

t n

m a = F

F

F

= G mM T n

R

2

R = R

T + h

a = G M T n

R

2

a = v 2

R n

+ dv

dt

t

dv = 0 dt
dv
= 0
dt

a

= v 2

 

R

m v 2

R

=

G mM T

R

2

v =

G · M T

R T +

h

3, 9 × 10 3 · 1

D

D = 2π(R T + h)

v T

T =

D

v

=

2π(R

T + h)

v

42 626 11 50 26

11 57 58

c = 3 × 10 8 · 1

L = c × t prec

L

t prec

t = ∆L

c

=

10

3 × 10

8

33

L = c × t

t = L

c

=

20 000 × 10

3

3 × 10

8

67

σ

9

σ = 33, 3 × 10 67 × 10

3

5, 0 × 10 5 %

µ

30 × 10 9 · 24 · 3600

t

=

68

38 × 10 6

· 1

36864

50

737 = 12 17

t

=